Parental Anxiety and Child Separation Anxiety: The Mediating Role of Overprotective Parenting - Kraus, Sabine; Hernández, Carlos; Kovács, Eszter (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to examine the mediating role of overprotective parenting in the relationship between parental anxiety and child separation anxiety. Methods and Materials: A descriptive correlational design was employed, with a sample of 410 parent–child dyads recruited from schools in Mexico using cluster random sampling. Participants included parents of children aged 7 to 12 years. Standardized questionnaires were used to measure parental anxiety, overprotective parenting, and child separation anxiety. Data analysis was conducted in two stages: Pearson correlation analysis using SPSS-27 to assess bivariate associations, and structural equation modeling (SEM) using AMOS-21 to test the hypothesized mediation model. Model fit was evaluated with multiple indices, including χ²/df, GFI, AGFI, CFI, TLI, and RMSEA. Findings: Correlation analyses showed that parental anxiety was significantly associated with both overprotective parenting (r = .48, p = .001) and child separation anxiety (r = .42, p = .002), while overprotective parenting was strongly related to child separation anxiety (r = .51, p < .001). SEM results indicated that the hypothesized model demonstrated good fit (χ² = 146.28, df = 84, χ²/df = 1.74, GFI = .94, AGFI = .91, CFI = .96, TLI = .95, RMSEA = .041). Path analysis revealed that parental anxiety significantly predicted overprotective parenting (β = .46, p < .001) and directly predicted child separation anxiety (β = .25, p = .004). Overprotective parenting significantly mediated the relationship, with an indirect effect of parental anxiety on child separation anxiety (β = .22, p = .002). Conclusion: The findings highlight overprotective parenting as a critical mechanism through which parental anxiety contributes to child separation anxiety. Interventions aimed at reducing parental overprotection and addressing parental anxiety may serve as effective strategies for preventing and alleviating separation anxiety in children.